2007
DOI: 10.1021/jm060928n
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of the First Selective Agonists for the Rat Vasopressin V1bReceptor:  Based on Modifications of Deamino-[Cys]arginine Vasopressin at Positions 4 and 8

Abstract: The neurohypophyseal peptides arginine vasopressin (AVP) and oxytocin (OT) mediate a wide variety of peripheral and central physiological and behavioral effects by acting on four different G-protein coupled receptors, termed V1a (vascular), V1b (pituitary), V2 (renal), and OT (uterine). We recently reported that d[Cha4]AVP (A), d[Leu4]AVP (B), d[Orn4]AVP (C), and d[Arg4]AVP (D) have high affinity and are selective agonists for the human V1b receptor. However, peptides A-D were subsequently shown to be potent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 104 publications
(318 reference statements)
0
23
0
Order By: Relevance
“…We designed and synthesized new short acting V 1a R selective analogues of general structure [Xaa 2 (68)) were tested by intravenous bolus in rats for duration of vasopressive action. Analogues 31,34,45,and 49 were as short-acting as AVP. Compound 45, FE 202158, is currently undergoing clinical trials in septic shock.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed and synthesized new short acting V 1a R selective analogues of general structure [Xaa 2 (68)) were tested by intravenous bolus in rats for duration of vasopressive action. Analogues 31,34,45,and 49 were as short-acting as AVP. Compound 45, FE 202158, is currently undergoing clinical trials in septic shock.…”
Section: ' Introductionmentioning
confidence: 99%
“…While no obvious SAR rules for the duration of action in vivo could be identified, compounds 20 and 68, which contain a cyclic aliphatic Cha residue in position 2, had considerably long duration of action. Compounds 31,34,45, and 49 displayed the most favorable overall pharmacological profile, and analogue 45 was selected for further evaluation as a potential treatment in critical care medicine. The differences in vasopressive duration of action in vivo for compounds 1, 2, and 45 are presented in Figure 3.…”
Section: ' Introductionmentioning
confidence: 99%
“…A selective V1b agonist was produced by replacement in AVP of the glutamine residue in position 4 by a leucine 18 and made highly resistant to degradation by deamination at the Cys 1 position. The subsequent replacement of Arg 8 by a Lys 8 , leading to the V1b agonist A 3,19,20 , did not modify its V1b selectivity. This allowed the covalent addition of a fluorophore to the free epsilon NH 2 group of the Lys residue at position 8 in A, thus making possible the synthesis of new fluorescent V1b agonists.…”
Section: Discussionmentioning
confidence: 83%
“…We used d[Leu 4 , Lys 8 ]VP (Peptide A in Fig 1, Tables I, II and III) as the parent molecule for designing fluorescent V1b analogues, since we had previously shown that this peptide is a V1b selective agonist both for rat and human VP/OT receptors 3,18,19 . First, we carried out the addition of an hydroxyl (OH) group at the N terminal position of d[Leu 4 ,Lys 8 ]VP to give [1-L-(−)-2-hydroxy-3-thiopropanoic acid, 4-leucine, 8-lysine]vasopressin ([HO 1 ][Leu 4 ,Lys 8 ]VP) (Peptide B in Tables I and II).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is possible that, under stimulated conditions, enough vasopressin is released into the supraoptic (and paraventricular) nucleus to increase the likelihood that any single vasopressin neuron will adopt phasic firing and so it will be important to determine the effects of vasopressin V 1a , V 1b and V 2 receptor antagonists on the activity of vasopressin neurons under such conditions. Vasopressin receptors have nanomolar affinity for vasopressin [40] and so hypothalamic vasopressin concentrations must be subnanomolar under basal conditions (otherwise all vasopressin neurons would be driven into phasic activity under basal conditions). Based on this observation, we can calculate the maximal secretion rate of vasopressin that must be evident under basal conditions.…”
Section: Modulation Of Spike Discharge Of Vasopressin Neurons By Somamentioning
confidence: 99%